2020
DOI: 10.1097/md.0000000000023095
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of traumatic out-of-hospital cardiac arrest patients according to the mechanism of injury

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Other authors have reported higher organ donation rates that ours, 25–28 but the available literature on the topic is highly heterogenous. Other authors reported rates of good neurological outcomes ranging between 4.5% and 79%, 4,5,17,21,23,29–31 and our results are within the highest (72.2%). This large range may be explained by the differences in the studied populations, and the fact that CPC are not recorded for all patients.…”
Section: Discussionsupporting
confidence: 73%
“…Other authors have reported higher organ donation rates that ours, 25–28 but the available literature on the topic is highly heterogenous. Other authors reported rates of good neurological outcomes ranging between 4.5% and 79%, 4,5,17,21,23,29–31 and our results are within the highest (72.2%). This large range may be explained by the differences in the studied populations, and the fact that CPC are not recorded for all patients.…”
Section: Discussionsupporting
confidence: 73%
“… 21 Despite these findings, neurological outcomes continue to be debated, as newer studies with larger numbers of survivors report good and moderate outcomes in only 4.3% to 27.0% of survivors. 22 23 The findings of the current review suggest that those who survive traumatic arrest may have a favorable prognosis. The observed improvement in neurological outcomes is likely connected to novel advances in damage control resuscitation and refinement of treatment of guidelines.…”
Section: Discussionmentioning
confidence: 86%
“…Whereas some cohort studies suggest that good outcomes can be achieved in select patient groups, especially in those with penetrating injuries, 31 32 other studies suggest that the mechanism of injury is not associated with better outcomes (neurological recovery or survival). 22 33 Hence, it would be valuable to assess the effect of the mechanism of injury on the neurological recovery following arrest. Although only a few studies assess traumatic arrest in the pediatric population, there is a general consensus that the functional outcomes are poorer compared with adults.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic cardiac arrest (TCA) is an uncommon cause of cardiac arrest and is associated with worse outcomes [ 11 ]. The reported survival rate of a traumatic out-of-hospital cardiac arrest is 1% to 7% [ 6 ]. However, there is increasing evidence that when potentially reversible causes are addressed early in the adult population, TCA survival rates are comparable to those reported in medical out-of-hospital cardiac arrests [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Refractory ventricular fibrillation (RVF) is described as the inability to obtain a return of spontaneous circulation (ROSC) within 10 min despite three defibrillation attempts, 300 mg of amiodarone, and 3 mg of epinephrine [ 4 ]. Trauma can present in multiple forms, and any of them can lead to a potentially reversible cause of cardiac arrest, from hypoxia, tension pneumothorax, hypovolaemia, or cardiac tamponade [ 5 - 6 ]. The pathophysiological mechanisms of VF are due to electrical reentry or increased automaticity, which is often a result of myocardial injury from an acute coronary syndrome (ACS).…”
Section: Introductionmentioning
confidence: 99%